Efektivitas Pemindahtanganan Aset Peralatan dan Mesin melalui Penjualan di Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Sidoarjo Provinsi Jawa Timur - Tumija, Tumija; Rachmadika, Frendymasta (Fakultas Manajemen Pemerintahan, Institut Pemerintahan Dalam Negeri, 2024)
Abstract One of the problems with Regional Property (BMD) owned by Sidoarjo Regency is that it is not used and is in a condition of serious damage. Another problem is the accumulation of heavily damaged assets which can be seen from the recorded value on the regional balance sheet, especially in the miscellaneous assets post. The aim of this research are to find out effectiveness of equipment and machinery assets redeployment through sale, inhibitants that are faced by Regional Finance and Assets Agency (BPKAD) of Sidoarjo Regency in realizing the effectiveness of equipment and machinery assets redeployment through sales. This research using qualitative descriptive method with inductive approach. Data was collected by interview technique complemented with documentation and observation. The result brought the fact that redeployment of equipment and machinery assets through sales in BPKAD Sidoarjo has fulfilled several dimensions of Gibson’s effectiveness theory even if it has not able yet to resolve the problem about the heap of heavy damaged equipment and maschinery assets completely. Equipment and machinery assets redeployment through sales has been done quite effectively although it still face faces obstacles such as lack of local government agency’s (OPD’s) understanding about assets redeployment, collecting and matching assets data, inadequate asset storage, dependency on state asset auction service (KPKNL) or public appraiser service (KJPP) because of unavailability of appraisers from the civil apparatus of Sidoarjo Government. Keywords: Effectiveness, Equipment and Machinery Assets, Redeployment through Sales Abstrak Permasalahan Barang Milik Daerah (BMD) yang dimiliki Kabupaten Sidoarjo salah satunya tidak terpakai dan dalam kondisi rusak berat. Masalah lain adanya penumpukan aset rusak berat dapat terlihat dari nilai tercatat pada neraca daerah khususnya pada pos aset lain-lain. Penelitian ini bertujuan untuk mendapatkan gambaran efektivitas pemindahtanganan aset peralatan dan mesin melalui penjualan, mengetahui hambatan yang dihadapi oleh Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Sidoarjo dalam mewujudkan efektivitas pemindahtanganan aset peralatan dan mesin melalui penjualan. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan induktif. Pengumpulan data dilakukan melalui teknik wawancara dilengkapi observasi dan dokumentasi. Hasil yang diperoleh penulis dalam penelitian ini yaitu pemindahtanganan aset peralatan dan mesin melalui penjualan di BPKAD Kabupaten Sidoarjo telah memenuhi sejumlah dimensi teori efektivitas Gibson meski belum mampu menyelesaikan masalah penumpukan aset peralatan dan mesin rusak berat secara tuntas. Pemindahtanaganan aset peralatan dan mesin melalui penjualan cukup efektif meski masih menghadapi hambatan meliputi kurangnya pemahaman organisasi perangkat daerah (OPD) terkait pemindahtanganan aset, pengumpulan dan pencocokan data aset, tempat penyimpanan yang belum memadai, ketergantungan pada KPKNL atau KJPP karena tidak adanya penilai dari aparatur Pemerintah Daerah Kabupaten Sidoarjo. Kata Kunci : Aset Peralatan dan Mesin, Efektivitas, Pemindahtanganan